Analysis of Partnership Principles of Small and Medium Enterprises (UKM) in BUMN Minister Regulation No. PER-05/04/2021 Against PT. Perkebunan Nusantara III Medan - Sunarto, Atika; Adnan, Muhammad Ali; Zulkifli, Suhaila (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research can be categorized as a type of observational legal research with a survey method. In observational research, the author makes direct observations in the field to collect information and data relevant to this research topic. Further, in terms of the nature of the research, it is descriptive in nature. This research was carried out in the PTPN III Medan environment, with the center of research attention being at PT. Nusantara Plantation III (PTPN III) Medan. The location of PTPN III Medan is located in the Medan area, and this company has become the focus of research because of its involvement in the implementation of the SOE Minister's regulations regarding partnerships with Small and Medium Enterprises (UKM) actors in the region. The data collected will be processed and grouped based on findings from research, interviews and questionnaires. Data analysis will involve interpreting the results, comparing them with the views of experts, as well as comparing them with applicable laws and regulations. The results of this analysis will help identify the implementation of the Minister of BUMN's regulations in the context of SME partnerships within PTPN III Medan based on dignified justice. Based on the conclusions, although the BUMN Ministerial Regulation provides an important framework, the weaknesses identified in the context of SME partnerships within PT. Perkebunan Nusantara III Medan needs to be addressed. Efforts to overcome these obstacles need to be carried out strategically, involving related parties including PTPN III and the government, to ensure that SME partnerships can run optimally according to the expected goals. The construction of BUMN Ministerial Regulation Number Per-05/Mbu/04/2021 regarding SME partnerships plays a vital role in ensuring partnerships that are based on fair, dignified and sustainable principles.